Plasmodium falciparum K13 expression associated with parasite clearance during artemisinin-based combination therapy - Silva, M. (2019)
Delayed parasite clearance and, consequently, reduced efficacy of artemisinin-based combination therapies have been linked with Plasmodium falciparum K13 gene SNPs in Southeast Asia. In Africa, significantly prolonged clearance has not yet been observed and the presently restricted variation in parasite clearance cannot be explained by K13 polymorphisms.